Acute arterial haemodynamics activation of endothelial to mesenchymal transition in long saphenous veins. Impact on vein graft disease. (3rd October 2022) - Ladak, S; McQueen, L; Joeldavid, L; Murphy, G; Zakkar, M
Abstract: Introduction: The long saphenous vein (LSV) is frequently used in cardiac surgery; however, its use is complicated by late stenosis or occlusion due to the development of intimal hyperplasia (IH). TGF-β has been implicated in the process of IH however the impact of acute haemodynamic changes on the activation of TGF-β endothelial-to mesenchymal transition (EndMT) has not been assessed and it's the focus of this study. Purpose: To assess the role of acute haemodynamics changes in veins implanted into arterial circulation on EndMT. Methods: Surplus LSV were exposed to acute arterial haemodynamics using a perfusion bioreactor. Changes in EndMT markers at the RNA and protein level evaluated by quantitative real time PCR, RNAScope and immunofluorescence. Results: The acute exposure of veins to arterial haemodynamics ex-vivo induced significant increase in inflammatory marker IL-8 expression and transcription factor TWIST1 in LSV (both p≤0.01, Figure 1A) endothelium. Furthermore, immunostaining demonstrated the activation of pSMAD (p≤0.01, Figure 1B) acutely in endothelium after 45 minutes of exposure to arterial haemodynamics. This was followed by significant increase of SMC related markers (Vimentin and α-SMA; Figure 1C, both p≤0.001) and the suppression of endothelial cell related marker CD31 after 4 hours of LSV exposure to acute arterial haemodynamics. RNAScope and IHC results showed localisation of TWIST1 RNA and protein in CD31+ (p≤0.001) and VECAD+ (p≤0.001) cells respectively following exposure to acute arterial haemodynamics (Figure 1D). Furthermore, TGF-β pathway phosphorylation array identified the activation of Smad1 (p≤0.05) but not TAK1 in LSV endothelial cells indicating that acute arterial haemodynamics activates the TGF-β–SMAD pathway specifically (Figure 1E). Conclusion: The exposure of LSV to acute arterial haemodynamics is associated with the activation of TGF-β–SMAD pathway leading to EndMT changes in the endothelium of vein grafts ex-vivo. This contributes to our understanding of the changes that occur in veins after implantation into arterial circulation and that the acute changes in the endothelium and suggests that strategies to modulate TGF-β–SMAD can be utilised to modulate IH in vein grafts. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Van Geest Foundation Heart and Cardiovascular Diseases Research Fund